A Randomized Double-Blind Placebo-Controlled Trial to Evaluate Prophylactic Effect of Traditional Chinese Medicine Supplementing Qi and Hemostasis Formula on Gastrointestinal Bleeding after Percutaneous Coronary Intervention in Patients at High Risks. (21st October 2018) - Zhang, Chenhao; Huang, Chaolian; Kong, Xiaolin; Liu, Guannan; Li, Ning; Liu, Jie; Zhang, Zongyao; Yang, Dawei; Liang, Chunling; Wang, Jie
Abstract : Objective . To evaluate the clinical efficacy of traditional Chinese medicine (TCM) supplementing Qi and hemostasis formula on gastrointestinal (GI) bleeding after percutaneous coronary intervention (PCI) and thus find out the optimal therapeutic regimen to reduce incidence of GI bleeding without increase of major adverse cardiovascular events (MACEs). Methods . In the randomized, double-blinded, controlled trial, 117 participants who underwent PCI were enrolled and evenly distributed into treatment arm (59) and control arm (58). Numerous end points were assessed including the primary endpoint of GI bleeding and MACEs and secondary endpoint of thromboelastogram (TEG) (mainly MAadp, inhibition of ADP, and inhibition of AA) and TCM syndrome score during the follow-up phase of 90 days. Results . Incidence of bleeding including GI bleeding and MACE did not differ significantly between two arms (28.82% in treatment arm versus 24.44% in control). However, on both days 30 and 90, TCM treatment remarkably reduced the TCM syndrome total score with notable alteration (P<0.05) except for some parameters such as pulse manifestation. When it came to TEG, however, M A A D P increased significantly on day 30 in control arm, accompanied by a notable descending in inhibition rate of ADP pathway (both P<0.01). Conclusion . (1) Supplementing Qi and hemostasis formula is equal to Pantoprazole Sodium Enteric-Coated Capsule in hemostasis and gastric mucosal protection; (2) supplementing Qi and hemostasis formula is superior to Pantoprazole Sodium Enteric-Coated Capsule in improving TCM syndrome manifestation possibly through the multitarget mechanism; (3) interference on clopidogrel of supplementing Qi and hemostasis formula might be much less than Pantoprazole Sodium Enteric-Coated Capsule due to the potential CYP450-independent mechanism. This trial is registered with ChiCTR1800014485 .